Applying Ecological Interface Design principles to the design of rural highway-rail grade crossing infrastructure. (September 2017) - Beanland, Vanessa; Grant, Eryn; Read, Gemma J. M.; Stevens, Nicholas; Thomas, Miles; Lenné, Michael G.; Stanton, Neville A.; Salmon, Paul M.
Countries such as Australia and USA have many rail level crossings (a.k.a. highway-rail grade crossings) with limited protection (e.g., static signs only or flashing lights but no physical barriers). Lower cost design solutions are required as upgrading crossings using current infrastructure treatments is cost-prohibitive. Here we applied Ecological Interface Design (EID) principles to develop a novel rail level crossing design for high-speed rural roads, and then evaluated the design via two driving simulator studies. Experiment 1 provided an initial concept evaluation of the crossing, then Experiment 2 evaluated the crossing in safetycritical situations, including when a distractor was present and when crossing infrastructure was damaged through vandalism. Driving performance, subjective workload, and usability were compared against existing rural crossing designs. Findings suggest the EID crossing provides a feasible alternative to existing designs, with the potential to encourage safer decision-making by road users and thus reduce collisions.